2020
DOI: 10.3354/meps13413
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the diet of beluga whales in response to changes in prey availability: insights on changes in the Beaufort Sea ecosystem

Abstract: The eastern Beaufort Sea (EBS) beluga whale Delphinapterus leucas population has experienced a 20 yr decline in inferred growth rates of individuals, which is hypothesized to have resulted from changes in prey availability. We used fatty acid signatures and stable isotope ratios to reconstruct the proportional contributions of 14 prey species to the diets of 178 beluga whales from 2011 to 2014. Prey estimates using quantitative fatty acid signature analysis suggest that EBS beluga whales primarily consume Arct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 74 publications
3
63
0
Order By: Relevance
“…The potential response of belugas to near‐future climate change may be a population‐specific combination of site fidelity and spatial flexibility, interacting with local or regional factors, such as prey availability, predation, and anthropogenic activities, which are all predicted to rapidly change as a consequence of climate change, and negatively impact beluga populations (Choy et al, 2020; Ferguson et al, 2010; Reeves et al, 2014; Small et al, 2017; Smith et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The potential response of belugas to near‐future climate change may be a population‐specific combination of site fidelity and spatial flexibility, interacting with local or regional factors, such as prey availability, predation, and anthropogenic activities, which are all predicted to rapidly change as a consequence of climate change, and negatively impact beluga populations (Choy et al, 2020; Ferguson et al, 2010; Reeves et al, 2014; Small et al, 2017; Smith et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In both polar regions, strong direct reliance on sea-ice derived organic matter has been shown in all ecosystem compartments, that is, sympagic (Søreide et al, 2006;Budge et al, 2008;Kohlbach et al, 2016;Kohlbach et al, 2017b), pelagic (Wang et al, 2015;Jia et al, 2016;Kohlbach et al, 2018;Schmidt et al, 2018;Kohlbach et al, 2019b), andbenthic (McMahon et al, 2006;Norkko et al, 2007;Søreide et al, 2013;Wing et al, 2018;Kohlbach et al, 2019a;Michel et al, 2019). Trophic linkages are not limited to primary consumers but extend to higher trophic levels (Bluhm and Gradinger, 2008;Kohlbach et al, 2017a;Brown et al, 2018;Choy et al, 2020) as indicated by the selection of icedependent species shown in Figure 4. In the Arctic Ocean, the under-ice fauna transfers the bulk of sympagic carbon to the pelagic system, and the contribution of the sea-ice meiofauna is very small (Ehrlich et al, 2021).…”
Section: Sea-ice Meiofauna and Under-ice Faunamentioning
confidence: 98%
“…Arctic cod (Boreogadus saida) is a critical carbon source for seabirds, fish, and marine mammals in high Arctic ecosystems (Bradstreet et al, 1986;Coad and Reist, 2004;Choy et al, 2020), many of which are key subsistence species harvested by northern communities (e.g., Inuvialuit communities; Harwood et al, 2015). Arctic cod has been reported as the most abundant fish species across a range of habitats (Rand and Logerwell, 2010;Hop and Gjøsaeter, 2013;Melnikov and Chernova, 2013;Walkusz et al, 2013;David et al, 2016;Majewski et al, 2017;Forster et al, 2020;Marsh et al, 2020).…”
Section: Key Carbon Transmitters In Ice-associated Food Webs Arctic Codmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicate circumpolar Arctic gadids are occurring at a lower frequency in the diets of common Arctic predators in the US–Canadian Arctic ( B . saida : Cusset et al., 2019; Choy et al., 2020) and European Arctic ( A. glacialis : Aschan et al., 2009). Reports also indicate that large numbers of fish in the sub‐Arctic are shifting towards the Russian zone of the Barents Sea and Kara Sea, but there is limited available catch data reported from the region to confirm this hypothesis (Chernova, 2018; Eriksen et al., 2020; Havforskningsrapporten, 2015; Mueter et al., 2016).…”
Section: Impacts Of Climate Change On the Movements Of Circumpolar Arctic Gadidsmentioning
confidence: 99%